Keragaman genetik mimi (Carcinoscorpius rotundicauda dan Tachypleus gigas) di perairan Demak, Madura dan Balikpapan berdasarkan penanda Random Amplified Polymorphic DNA - NAILA KHURIL AINI; ALI MASHAR; Hawis H. MADDUPPA; YUSLI WARDIATNO (Graduate School Bogor Agricultural University (SPs IPB), 2020)
Horseshoe crab is an exotic and protected marine organism in Indonesia and is considered as the living fossil animal in the world. IUCN conservation status of Carcinoscorpius rotundicauda and Tachypleus gigas is still Data Deficient, and in Indonesia research on genetic population is lacking, if any. This study aims to reveal genetic diversity of C. rotundicauda and T. gigas populations in northern Java (Demak and Madura) and Balikpapan waters. This research was conducted by using molecular analysis with genetic markers Random Amplified Polymorphic DNA (RAPD). The primers used in this study were OPB 06, OPG 10, and OPX 03. The results showed that the highest polymorphism of C. rotundicauda was found in Demak (74.6667%) and heterozygosity was 0.2669. Furthermore, T. gigas had the highest polymorphism in Madura (74.3590%) and heterozygosity was 0.25551. Based on pairwise comparison tests, populations of C. rotundicauda and T. gigas in Demak, Madura, and Balikpapan were significantly different (p<0.05). The difference is believed due to the limitation movement of horseshoe crabs from and into the three locations, as well as the presence of natural geographic barrier. Thus,it can be concluded that horseshoe crabs in northern Java and Balikpapan waters has different genetic diversity. Genetically, horseshoe crab in northern Java or Balikpapan had relatively moderate diversity and low adaptation capability.